L’impatto del nuovo Codice del Terzo settore sulla disciplina degli “enti religiosi” (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. Gli “enti ecclesiastici” fra legge delega e decreto legislativo - 2. Questioni di nome - 3. Questioni di sostanza - 4. Gli enti ecclesiastici civilmente riconosciuti sono enti del Terzo settore? - 5. Cenni alla disciplina tributaria.The impact of the new “Third Sector Code” on the regulation of “religious bodies”.ABSTRACT: Italian Law regulates in a special way “ecclesiastical bodies”, the entities that have been recognized as “legal person” by the Law of the State according to the bilateral agreements signed in conformity with Italian Constitution. Nevertheless, these entities are regulated as well by other laws regarding their “not religious” activities, such as social assistance, education (as schools and universities), health care (as hospitals and retirement communities). On July 2017 has been adopted a new Law on the so called “Third Sector”, that impacts on the current legislation in several points. In this essay, I discuss the legitimacy of the adopted denomination of “religious bodies” instead of “ecclesiastical bodies”, that it is not a mere nominalist issue, because it changes many rules. Then I examine the practical implications related to this new legal expression, wondering if those religious/ecclesiastical bodies are “Third Sector entities”. In my opinion, the answer is negative. In the last paragraph, I address the consequences of the new “Third Sector Code” on tax aspects.